The driver landscape of sporadic chordoma. Issue 1 (December 2017) - Tarpey, Patrick; Behjati, Sam; Young, Matthew; Martincorena, Inigo; Alexandrov, Ludmil; Farndon, Sarah; Guzzo, Charlotte; Hardy, Claire; Latimer, Calli; Butler, Adam; Teague, Jon; Shlien, Adam; et al.
Abstract Chordoma is a malignant, often incurable bone tumour showing notochordal differentiation. Here, we defined the somatic driver landscape of 104 cases of sporadic chordoma. We reveal somatic duplications of the notochordal transcription factor brachyury (T ) in up to 27% of cases. These variants recapitulate the rearrangement architecture of the pathogenic germline duplications ofT that underlie familial chordoma. In addition, we find potentially clinically actionable PI3K signalling mutations in 16% of cases. Intriguingly, one of the most frequently altered genes, mutated exclusively by inactivating mutation, wasLYST (10%), which may represent a novel cancer gene in chordoma. Chordoma is a rare often incurable malignant bone tumour. Here, the authors investigate driver mutations of sporadic chordoma in 104 cases, revealing duplications in notochordal transcription factor brachyury (T ), PI3K signalling mutations, and mutations in LYST, a potential novel cancer gene in chordoma.